Growing Insight In Public Relations Marketing In Housewives Who Are Owners Of Small Micro Businesses In Bulusan Semarang City - Nunik Kusnilawati (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
: To be able to become a strong and reliable entrepreneur, hard skills and soft skills are needed, this is also needed by micro-small businesses. Marketing public relations is needed as knowledge to open insight for every entrepreneur so that they can develop, because knowledge about marketing public relations will support success in producing and marketing products through product image and business image. Based on observations of micro-small scale businesses in Bulusan Subdistrict, Tembalang District, Semarang, suboptimal business performance is related to limited knowledge about creating product images and business images to build relationships with consumers and understand their needs. By developing insight into marketing public relations, it is hoped that they will become aware of the strategic role and importance of product image and business image, so that they will ultimately be able to market products/services to meet consumer needs in a sustainable manner. Keywords: insight into marketing public relations, business image, product image